2014
DOI: 10.1111/ldrp.12030
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Writing Difficulties in First Grade: An Investigation of Writing and Reading Measures

Abstract: Early identification of students who are at risk for writing difficulties is an important first step in improving writing performance. First grade students (N = 150) were administered a set of early writing measures and reading measures in January. Sentence Writing Quality and Oral Reading Fluency demonstrated strong classification accuracy when a Teacher Rating was used to identify which students had writing difficulties (AUC > .90), and the combined measures yielded sensitivity and specificity indices exceed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 47 publications
3
27
0
1
Order By: Relevance
“…Later studies revealed that word spelling as measured by a word dictation (WD) task, was accurate at identifying students at risk for literacy problems in first grade (AUC = 0.780-0.873; Ritchey & Coker, 2014). Lembke et al (2003) found that WD had the strongest criterion validity in second grade compared with other copying and dictation tasks (r = 0.80-0.92).…”
Section: Cbm-w Tasksmentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies revealed that word spelling as measured by a word dictation (WD) task, was accurate at identifying students at risk for literacy problems in first grade (AUC = 0.780-0.873; Ritchey & Coker, 2014). Lembke et al (2003) found that WD had the strongest criterion validity in second grade compared with other copying and dictation tasks (r = 0.80-0.92).…”
Section: Cbm-w Tasksmentioning
confidence: 99%
“…Studies have indicated that tasks involving letter‐, word‐, and sentence‐level copying, dictation, and novel writing, where participants generate their own sentences instead of copying or taking dictation, are more reliable and valid for Kindergarten through third grade as compared with the late elementary grades (Coker & Ritchey, ; Lembke et al, ; McMaster & Campbell, ; McMaster et al, ; Ritchey, ; Ritchey & Coker, , ). Ritchey () found that letter writing, sound spelling, and word spelling were reliable ( r = 0.89–0.92) and valid ( r = 0.27–0.81) tasks to measure writing skills in Kindergarten at a single point in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be most effective, CBM should have evidence that it is technically adequate and sensitive to change across time, allowing it to be used both as a universal screener and as a tool to monitor student progress (Deno et al, 2009). While CBM-W tasks designed to assess passage-level composition (e.g., story, picture, and photo prompts) demonstrate evidence of technical adequacy and face validity for students in third grade and above (McMaster, Du, & Pétursdóttir, 2009; McMaster et al, 2011; Ritchey & Coker, 2014), research indicates that sentence-level tasks (e.g., picture word, sentence copying, and sentence writing tasks) are more appropriate for students in the early elementary grades (Coker & Ritchey, 2014; Lembke, Deno, & Hall, 2003; McMaster et al, 2009; McMaster et al, 2011; Ritchey & Coker, 2014).…”
Section: Cbm-wmentioning
confidence: 99%
“…Each of these scoring methods shared similarities with scoring of general writing samples (Koutsoftas & Gray, 2012;Olinghouse & Wilson, 2013). We did not, however, locate any MW assessments in which student work was scored according to writing curriculum-based measurement (CBM) recommendations, such as percentage of correct word sequences, which is often described as an effective method for scoring the writing of students with or at-risk for learning difficulties (McMaster, Du, Parker, & Pinto, 2011;Ritchey & Coker, 2014).…”
Section: Mathematics-writing Assessmentsmentioning
confidence: 99%